Dexamethasone as an Analgesic Adjunct for Postcesarean Delivery Pain: A Randomized Controlled Trial. (24th September 2021) - Mehdiratta, Jennifer E.; Dominguez, Jennifer E.; Li, Yi-Ju; Saab, Remie; Habib, Ashraf S.; Allen, Terrence K.
Abstract : Objectives . Dexamethasone has been shown to have analgesic properties in the general surgical population. However, the analgesic effects for women that undergo cesarean deliveries under spinal anesthesia remain unclear and may be related to the timing of dexamethasone administration. We hypothesized that intravenous dexamethasone administered before skin incision would significantly reduce postoperative opioid consumption at 24 h after cesarean delivery under spinal anesthesia with intrathecal morphine. Methods . Women undergoing elective cesarean deliveries under spinal anesthesia were randomly assigned to receive 8 mg of intravenous dexamethasone or placebo prior to skin incision. Both groups received a standardized spinal anesthetic and multimodal postoperative analgesic regime. The primary outcome was cumulative opioid consumption at 24 h. Secondary outcomes included cumulative opioid consumption at 48 h, time to first analgesic request, and pain scores at rest and on movement at 2, 24, and 48 h. Results . 47 patients were analyzed—23 subjects that received dexamethasone and 24 subjects that received placebo. There was no difference in the median (Q1, Q3) cumulative opioid consumption in the first 24 hours following cesarean delivery between the dexamethasone group 15 (7.5, 20.0) mg and the placebo group 13.75 (2.5, 31.25) mg (P = 0.740 ). There were no differences between the groups in cumulative opioid consumption at 48 h, time to first analgesic request, and pain scores. Conclusions . Intravenous dexamethasone 8 mg administered prior to skin incision did not reduce the opioid consumption of women that underwent cesarean deliveries under spinal anesthesia with intrathecal morphine and multimodal postoperative analgesic regimen.